Mendelian Randomization Analyses Identified Bioavailable Testosterone Mediates the Effect of Fat Intake on Prostate Cancer - Du, Qiao; Wang, Xia; Yang, Hao; Luo, Zheng; Xu, Youqi (Journal of Contemporary Medical Practice, 2024)
Background: Dietary factors are considered significant in the risk of prostate cancer (PCa). However, observational studies concerning the influence of macronutrients and micronutrients on PCa risk have yielded inconsistent findings. Method: We employed a two-sample Mendelian randomization (MR) approach to assess the impacts of four principal macronutrients and 17 micronutrients on PCa risk. Utilizing MR, we examined the relationship between fat digestion products (glycerol, fatty acids) and PCa, and conducted a two-step MR to determine if serum testosterone mediates the impact of fat intake on PCa risk. Results: Our study revealed a strong association between genetically predicted fat intake and PCa risk [OR=1.818, 95% CI (1.136, 2.909), P=0.013], with evidence suggesting that vitamin B5, vitamin B12, carotenoids, and zinc may influence PCa risk. No genetic evidence linked glycerol and various fatty acids to PCa risk (all P>0.05). Notably, the mediator bioavailable testosterone explained of the total effect of fat intake on prostate cancer risk [mediated proportion=8.8 %, 95% CI (-4.4% , 21.9%)]. Conclusion: In conclusion, our research demonstrates that fat intake increases the risk of prostate cancer. We also provide genetic evidence that bioavailable serum testosterone mediates the effect of fat consumption on prostate cancer risk. However, we found no significant benefits from micronutrients in preventing prostate cancer, with the exception of carotenoids.